Ammonium ultra-selective membranes for wastewater treatment and nutrient enrichment: Interplay of surface charge and hydrophilicity on fouling propensity and ammonium rejection. (15th February 2021) - Bao, Xian; She, Qianhong; Long, Wei; Wu, Qinglian
Highlights: Ultrahigh ammonium rejection of 94.83% for domestic wastewater is achieved Ammonium rejection is related to ammonium selectivity and anti-fouling capacity Competing effect of hydrophilicity and potential on fouling is investigated Over-loading primary amine aggravates membrane fouling Primary amine enhances fouling reversibility and ammonium rejection recovery Abstract: Membrane fouling and ammonium transmembrane diffusion simultaneously pose great challenges in membrane-based pre-concentration of domestic wastewater for efficient subsequent resources recovery (i.e., energy and nutrients). Herein, amine-functionalized osmotic membranes were fabricated by optimizing the grafting pathway of polyamidoamine (PAMAM) dendrimer to mitigate fouling and ammonium transmembrane diffusion. Compared to the control membrane, the PAMAM-grafted membranes with abundant primary amine groups possessed substantially increased hydrophilicity and positive charges (i.e., protonated primary amines) and thus exhibited superior anti-fouling capability and ammonium selectivity. With further increasing the PAMAM grafting ratio, the membrane exhibited a steady enhancement in ammonium selectivity and eventually achieved an ultra-high ammonium rejection of 99.4%. Nevertheless, the anti-fouling capability of such ammonium ultra-selective membrane was weakened due to the suppression of the adverse impact of excessive positive charges over the beneficial effect of increased surface hydrophilicity. This in turn leads to a drop of ammonium rejection below 90% during domestic wastewater concentration. This study demonstrates that the membrane with a moderate primary amine loading could achieve the highest anti-fouling capability with only less than 10% flux decline and meanwhile maintain an excellent ammonium rejection above 94% during raw domestic wastewater concentration. This work provides theoretical guidance for fabricating simultaneously enhanced anti-fouling and ammonia-rejecting membranes. Graphical Abstract: Image, graphical abstract